Cataract Surgical Planning Using Online Software vs Traditional Methods: A Time/Motion and Quality of Care Study [Corrigendum] - Gujral T (Dove Medical Press, 2021)
Gujral T, Hovanesian J. Clin Ophthalmol. 2021;15:3197–3203.The authors have advised that the funding statement on page 3203 is incorrect. The text “Alcon” should read “Carl Zeiss Meditec”.The authors apologize for this error.Read the original article